Overestimated renal function in patients with liver cirrhosis predicts poor prognosis. Issue 7 (19th April 2022) - Yoshida, Sonoe; Suda, Goki; Ohara, Masatsugu; Kimura, Megumi; Yang, Zijian; Maehara, Osamu; Fu, Qingjie; Hosoda, Shunichi; Akinori, Kubo; Tokuchi, Yoshimasa; Yamada, Ren; Kitagataya, Takashi; et al.
Abstract: Aim: A high prevalence of overestimated renal function in patients with liver cirrhosis (LC) has been reported; nonetheless, its impact on prognosis remains unclear. We aimed to evaluate the impact of overestimated renal function on prognosis in patients with LC. Methods: An overestimated renal function was defined as a >20% increase in the creatinine‐based estimated glomerular filtration rate (eGFR), compared with cystatin C‐based eGFR. LC patients with conserved serum, who were evaluated for muscle atrophy and had proper clinical information were included, and their prognostic factors were analyzed. Results: A total of 215 consecutive patients with LC were included. The prevalence of overestimated renal function was 29.8% (64/215). Kaplan‐Meier survival analysis revealed that patients with overestimated renal function had a poorer prognosis than those without overestimated renal function (hazard ratio [HR]: 2.217 95% confidence interval [CI]: 1.290–3.810; p = 0.001). Subgroup analysis showed that overestimated renal function was a significant prognostic factor, irrespective of sex and the presence of hepatocellular carcinoma (HCC). Multivariate Cox regression analyses revealed that overestimated renal function was a significant and independent factor predictive of poor prognosis in the entire cohort (HR: 2.050; 95% CI: 1.041–4.037; p = 0.038) and in subgroups classified by Child‐Pugh class A (HR: 2.131; 95% CI: 1.019–4.458; p = 0.044), Model for End‐Stage Liver Disease score ≤9 (HR: 2.303; 95% CI: 1.038–5.109; p = 0.04), and presence of HCC (HR: 2.290; 95% CI: 1.128–4.651; p = 0.022). Conclusion: Overestimated renal function is a significant and independent prognostic factor in patients with LC.